Patent Foramen Ovale and Diving - Şefika KÖRPINAR (Bezmiâlem Science, 2019)

(untitled)
Although patent foramen ovale (PFO) was anatomically depicted in 1513 by Leonardo da Vinci and described as a thromboembolism route in 1877, it has been ignored for a long time as a potential way to produce pathological conditions. The unifying hypothesis associated with multiple clinical issues, such as cryptogenic stroke, migraine and decompression sickness is that a particle, inert gas bubbles or chemical substance in the venous circulation bypasses the lungs and enters to the systemic circulation via PFO. In this review, current data on the status of PFO in diving medicine are discussed.